Barely visible impact damage identification in a 3D core sandwich structure - Sikdar, Shirsendu; Ostachowicz, Wiesław; Kudela, Paweł; Radzieński, Maciej (Computer Assisted Methods in Engineering and Science, 2017)
3D core sandwich structure (3DCSS) is a popular lightweight construction material in the automotive, aerospace and marine industries. However, barely visible low-speed impact-damage (BVLID) may occur in the 3DCSS due to foreign-object-impact that can significantly reduce the load-bearing capacity of the structure. This paper presents a guided wave (GW) propagation based BVLID identification technique for the 3DCSS. A global-matrix formulation based semi-analytical model is applied to generate the dispersion curve for the GW propagation in the 3DCSS. It is observed that the GW propagation in the 3DCSS is multi-modal in nature. Finite-element numerical simulation of GW propagation in the 3DCSS is carried out in Abaqus. A significant increment in the primary antisymmetric mode is noticed due to the presence of BVLID region in the structure. Experiments are then conducted on a 3DCSS sample to validate the simulation results. There is a good agreement between the simulation and experimental results in all the cases.